Reconstruction automatique des entités d’un modèle BREP à partir d’un maillage déformé - Lohichi, Borhen; BenAmara, Abdelmajid; François, Vincent (European Journal of Computational Mechanics, 2009)
Nowadays, the integration of the different steps of mechanical design process (Design, analysis and manufacturing) is a necessity to reduce the time of design and optimization. This tendency of integrating CAD/CAM/Analysis and automation of the corresponding processes requires shared data between the various tasks using an integrated product model. Our research is oriented to CAD/CAM/Analysis integration by rebuilding the CAD model (BREP) starting from the FE results (deformed mesh). This paper presents techniques for rebuilding the geometrical and topological entities of the CAD model starting from a deformed mesh.